Cytotoxic effect of jasmonate and methyl jasmonate on a canine macrophage tumor cell line Efeito citotóxico de jasmonato e metiljasmonato em linhagem tumoral celular de macrófagos caninos - C. Hernandes; G.P. Cardozo; S.C. França; A.L. Fachin; M. Marins; M.V Lourenço (Universidade Estadual Paulista, 2012)
Cancer is one of the leading causes of death in dogs, a fact that has boosted the investigation for new more specific antitumor drugs. This study evaluated the antitumor activity of jasmonates in the canine macrophage cell line DH82 (ATCC # CRL-10389) isolated from a case of malignant histiocytoma. The activities of methyl jasmonate and jasmonic acid were compared to that of doxorubicin by the MTT assay. Methyl jasmonate resulted in the highest inhibition of cell growth (82.2%), followed by doxorubicin (80.7%) and jasmonic acid (36.5%). More detailed studies regarding the action of jasmonates on animal health are necessary, but the present results indicate methyl jasmonate as an alternative to the development of drugs for the treatment of canine oncologies. O câncer é uma das principais causas de morte em cães o que tem impulsionado a pesquisa por novos antitumorais com ação mais específica. Neste trabalho, a atividade antitumoral de jasmonatos foi avaliada na linhagem de macrófagos caninos DH82 (ATCC # CRL-10389), a qual é originada de um caso de histiocitoma maligno. A atividade do metil jasmonato (MJ) e do ácido jasmônico (AJ) foram comparadas à doxorrubicina, através do método de coloração MTT. O MJ apresentou maior inibição (82,2%), seguido da Doxorrubicina (80,7%) e AJ (36,5%). Estudos mais completos da ação dos jasmonatos na saúde animal ainda são necessários, porém, os dados deste trabalho apontam o MJ como alternativa para o desenvolvimento de drogas para o tratamento das oncologias caninas.